Disentangling the microfoundations of acquisition behavior and performance - Meyer-Doyle, Philipp; Lee, Sunkee; Helfat, Constance E. (Strategic Management Journal, 2019)
[Research Summary:The acquisition literature has highlighted that both firm-level and manager-level factors shape acquisition outcomes, yet little is known about their relative contribution. We conduct a variance decomposition analysis to explore the contribution of CEO-level versus firm-level factors to acquisition behavior and performance. We also extend the methodology of variance decomposition in strategic management research by employing Poisson multi-level models, and deriving the percentage of variance attributable to each level in a four-level model. Although CEO and firm effects both explain a substantial share of the variance in acquisition behavior, the CEO-effect is notably larger. CEO-level factors also drive a large portion of the variance in acquisition performance. Overall, our study contributes to the literatures on acquisitions and variance decomposition, and has implications for dynamic capabilities. Managerial Summary:How much do firm-level factors and CEO-level factors matter for explaining acquisition behavior and acquisition performance? This question is not only relevant for researchers but also for practitioners who seek to better understand what drives acquisitions and their outcomes. To help answer this question, our study conducts a variance decomposition analysis of acquisition behavior and acquisition performance. We find that both CEO-level factors and firm-level factors explain a substantial portion of the variance in acquisition behavior, but that CEO-level factors matter relatively more. We also find that CEO-level factors also explain a substantial portion of the variance in acquisition performance.]